Without using trigonometric tables, evaluate the following:
(sin 49°cos 41°)2+(cos 41°sin 49°)2\Big(\dfrac{\text{sin 49°}}{\text{cos 41°}}\Big)^2 + \Big(\dfrac{\text{cos 41°}}{\text{sin 49°}}\Big)^2(cos 41°sin 49°)2+(sin 49°cos 41°)2
12 Likes
Solving,
⇒(sin 49°cos 41°)2+(cos 41°sin 49°)2⇒(sin (90° - 41°)cos 41°)2+(cos 41°sin (90° - 41°))2As, sin (90 - θ) = cos θ⇒(cos 41°cos 41°)2+(cos 41°cos 41°)2⇒12+12⇒1+1⇒2.\Rightarrow \Big(\dfrac{\text{sin 49°}}{\text{cos 41°}}\Big)^2 + \Big(\dfrac{\text{cos 41°}}{\text{sin 49°}}\Big)^2 \\[1em] \Rightarrow \Big(\dfrac{\text{sin (90° - 41°)}}{\text{cos 41°}}\Big)^2 + \Big(\dfrac{\text{cos 41°}}{\text{sin (90° - 41°)}}\Big)^2 \\[1em] \text{As, sin (90 - θ) = cos θ} \\[1em] \Rightarrow \Big(\dfrac{\text{cos 41°}}{\text{cos 41°}}\Big)^2 + \Big(\dfrac{\text{cos 41°}}{\text{cos 41°}}\Big)^2 \\[1em] \Rightarrow 1^2 + 1^2 \\[1em] \Rightarrow 1 + 1 \\[1em] \Rightarrow 2.⇒(cos 41°sin 49°)2+(sin 49°cos 41°)2⇒(cos 41°sin (90° - 41°))2+(sin (90° - 41°)cos 41°)2As, sin (90 - θ) = cos θ⇒(cos 41°cos 41°)2+(cos 41°cos 41°)2⇒12+12⇒1+1⇒2.
Hence, (sin 49°cos 41°)2+(cos 41°sin 49°)2=2.\Big(\dfrac{\text{sin 49°}}{\text{cos 41°}}\Big)^2 + \Big(\dfrac{\text{cos 41°}}{\text{sin 49°}}\Big)^2 = 2.(cos 41°sin 49°)2+(sin 49°cos 41°)2=2.
Answered By
5 Likes
cosec 17°30′sec 72° 30′\dfrac{\text{cosec 17°30}'}{\text{sec 72° 30}'}sec 72° 30′cosec 17°30′.
cot 40°tan 50°−12(cos 35°sin 55°)\dfrac{\text{cot 40°}}{\text{tan 50°}} - \dfrac{1}{2}\Big(\dfrac{\text{cos 35°}}{\text{sin 55°}}\Big)tan 50°cot 40°−21(sin 55°cos 35°)
sin 72°cos 18°−sec 32°cosec 58°\dfrac{\text{sin 72°}}{\text{cos 18°}} - \dfrac{\text{sec 32°}}{\text{cosec 58°}}cos 18°sin 72°−cosec 58°sec 32°
cos 75°sin 15°+sin 12°cos 78°−cos 18°sin 72°\dfrac{\text{cos 75°}}{\text{sin 15°}} + \dfrac{\text{sin 12°}}{\text{cos 78°}} - \dfrac{\text{cos 18°}}{\text{sin 72°}}sin 15°cos 75°+cos 78°sin 12°−sin 72°cos 18°